Faktor Sosial-Ekonomi dan Kesadaran Hukum sebagai Penentu Perilaku Masyarakat terhadap Perdagangan llegal Gading Gajah di Sawang, Aceh Utara - Yusmadi, Yusmadi; Ridwan Iriadi; Sitti Zubaidah (Fakultas Biologi Universitas Gadjah Mada, 2026)
Illegal ivory trade persists in Sawang Subdistrict, North Aceh, despite the legal protection of the Sumatran elephant (Elephas maximus sumatranus). This study aims to analyze the driving factors and community legal awareness regarding illegal ivory trade. A quantitative descriptive–correlational approach was employed using a cross-sectional survey of 120 respondents selected through stratified random sampling. Data were collected via structured questionnaires and analyzed using multiple linear regression. Results indicate that community legal awareness is low (composite score = 35), with only 46.2% of respondents aware that elephants are legally protected and merely 12.3% understanding the criminal sanctions for ivory trade. Key driving factors include economic pressure, socio-cultural dynamics, and limited access to information. Regression analysis confirmed all three factors significantly influence low legal awareness (p < 0.05), with information access being the strongest predictor (β = 1.253). The study concludes that repressive law enforcement alone is insufficient to curb illegal ivory trade. Policy recommendations include: (1) integrating Islamic and customary values into conservation education through religious and traditional leaders; (2) developing sustainable alternative livelihoods such as community-based ecotourism; and (3) strengthening local reporting mechanisms via SMS gateway and community radio.